Russian Verbal Prefixation and Semantic Features An Analysis of the Prefix vz- - Gallant, James (Slavistische Beitraege, 1979)
This study advances a theory that verbal prefixation is a device for displaying the action of the verb in relationship to an abstract conceptual system which can be represented in geometric terms as a framework consisting of two primary axes, a horizontal and a vertical, plus derivative planes and volumes.